2013
DOI: 10.1002/asjc.704
|View full text |Cite
|
Sign up to set email alerts
|

Square‐Root Cubature‐Quadrature Kalman Filter

Abstract: In this paper, an on-going work introducing square-root extension of cubature-quadrature based Kalman filter is reported. The proposed method is named square-root cubature-quadrature Kalman filter (SR-CQKF). Unlike ordinary cubature-quadrature Kalman filter (CQKF), the proposed method propagates and updates square-root of the error covariance without performing Cholesky decomposition at each step. Moreover SR-CQKF ensures positive semi-definiteness of the state covariance matrix. With the help of two examples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 13 publications
(24 reference statements)
0
23
0
Order By: Relevance
“…Others have tried to select the sample size adaptively over time [23,14,4,22,12]. Kullback-Leibler distance (KLD) sampling [4,22] is the other efficient method that is utilized here as well for adaptive adjustment of the sample size in CQPF.…”
Section: Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…Others have tried to select the sample size adaptively over time [23,14,4,22,12]. Kullback-Leibler distance (KLD) sampling [4,22] is the other efficient method that is utilized here as well for adaptive adjustment of the sample size in CQPF.…”
Section: Nomenclaturementioning
confidence: 99%
“…CQKF has been presented as a novel algorithm where the multivariate moment integral is computed numerically using the third-order cubature rule and multiple Gauss-Laguerre quadrature points [2]. As a more generalized form of the cubature Kalman filter (CKF) [1], the CQKF has two implementation variants: standard CQKF and the square root CQKF (SR-CQKF) [3]. Unlike ordinary CQKF, the SR-CQKF propagates and updates square root of the error covariance and ensures positive semi-definiteness of the state covariance matrix.…”
Section: Nomenclaturementioning
confidence: 99%
“…The conventional CQKF suffers significant numerical errors in matrix inversion for higher probability of delay (p) and hence its square-root version [16] is used for implementation. From the plots, it could be concluded that the performance of CQKF-RD is significantly better than the ordinary CQKF, in the presence of a delay.…”
Section: A Problemmentioning
confidence: 99%
“…The simulation results show that SSRCKF can achieve more accurate results compared with CKF for high-dimensional system. Bhaumik [15,16] adopts -order generalized Gauss-Laguerre quadrature rule to calculate the radial integral and puts forward the cubature quadrature Kalman filter (CQKF). It is pointed out that CQKF is the generalized form of CKF; that is, CKF is the simplified form of CQKF with the first-order Gauss-Laguerre quadrature rule.…”
Section: Introductionmentioning
confidence: 99%